Effectiveness of laddered embossed structure in a locking compression plate for biodegradable orthopaedic implants. (February 2022) - Chandra, Girish; Pandey, Ajay
Locking compression plate (LCP) has conventionally been the most extensively employed plate in internal fixation bone implants used in orthopaedic applications. LCP is usually made up of non-biodegradable materials that have a higher mechanical capability. Biodegradable materials, by and large, have less mechanical strength at the point of implantation and lose strength even more after a few months of continuous degradation in the physiological environment. To attain the adequate mechanical capability of a biodegradable bone implant plate, LCP has been modified by adding laddered – type semicircular filleted embossed structure. This improved design may be named as laddered embossed locking compression plate (LELCP). It is likely to provide additional mechanical strength with the most eligible biodegradable material, namely, Mg-alloy, even after continuous degradation that results in diminished thickness. For mechanical validation and comparison of LELCP made up of Mg-alloy, four-point bending test (4PBT) and axial compressive test (ACT) have been performed on LELCP, LCP and continuously degraded LELCP (CD-LELCP) with the aid of finite element method (FEM) for the assembly of bone segments, plate and screw segments. LELCP, when subjected to the above mentioned two tests, has been observed to provide 26% and 10.4% lower equivalent stress, respectively, than LCP without degradation. It is also observed mechanically safe and capable of up to 2 and 6 months of continuous degradation (uniform reduction in thickness) for 4PBT and ACT, respectively. These results have also been found reasonably accurate through real-time surgical simulations by approaching the most optimal mesh. According to these improved mechanical performance parameters, LELCP may be used or considered as a viable biodegradable implant plate option in the future after real life or in vivo validation.